Analysis of Learning Motivation of Third-Semester Students in the Islamic Religious Education Study Program at STAI Al-Gazali Soppeng - Risma Handayani; Reski Nurul Fajri; Nurnanensi Nurnanensi; Selvianti Selvianti; Bil Khair; Muhammad Zulfikar; Muh Yusuf (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Learning motivation is one of the important factors that determine whether a student can succeed in college, especially for students of the Islamic Religious Education Study Program who must balance academic learning and religious values. This study aims to understand the learning motivation of third-semester students of the Islamic Religious Education Study Program at STAI Al-Gazali Soppeng, as well as the factors that influence this motivation. This study used a qualitative approach with descriptive methods. Data were collected through observation, in-depth interviews, and documentation of students selected purposively. Data analysis was carried out in three stages: data reduction, data presentation, and conclusion drawing. The results show that student learning motivation is influenced by internal factors such as learning interests, ideals, and religious awareness, as well as external factors such as the teaching methods of lecturers, the learning environment, and support from surrounding communities. These findings indicate that student learning motivation is in the fairly good category, but still needs to be improved. This study emphasizes the importance of innovation in teaching methods and guidance that combine academic and spiritual to continuously strengthen student learning motivation.